Patients’ experiences of a Virtual Fracture Assessment Clinic Pathway: A qualitative study - Darragh Carolan; Shane O’Neill; Breon White; Frank Lyons; Grainne Colgan; Vinny Ramiah; Dervilla Danaher; Gillian Yeowell (PLoS ONE, 2025)
Background and objectives Existing literature has demonstrated the efficacy of a virtual fracture assessment clinic pathway, however there is limited research exploring patients’ experiences of a complete pathway, from initial presentation at the Emergency Department or Injury Unit to discharge. The aim of this study was to explore the experiences of patients who have recently sustained a stable peripheral limb fracture, having received care across a complete virtual fracture assessment clinic pathway, in order to improve patient care. Methods One-to-one semi-structured interviews were completed via recorded phone and video calls, with a purposive sample of 12 participants. Interviews were completed until data saturation was achieved. Interviews were transcribed verbatim and data was analysed using thematic analysis. Results Six overarching themes were identified; ‘trust’ (in the pathway and management plan), ‘conflicting advice’ (on diagnosis and management plan), ‘information’ (need for more basic information), ‘severity of injury’ (participants’ perceptions of the severity of their injuries), ‘reassurance’ (through follow-up x-rays and physiotherapy consultations) and ‘efficiency’. Conclusions This is the first qualitative study exploring patients’ experiences of a complete virtual fracture assessment clinic pathway. Patients’ experiences may be improved through patient education on the pathway process and providing standardised injury-specific patient information documentation. Regular communication between different healthcare professionals involved in the pathway may reduce conflicting advice. Developing an opt-in physiotherapy service and providing patients with a standardised text message informing patients when their virtual consultation will occur may also improve patients’ experience of the pathway. Establishing a referral pathway with a fracture liaison service is also recommended to further enhance a virtual fracture assessment clinic pathway. Future research is needed to investigate how therapeutic relationships can be developed when care is delivered virtually and to explore the experiences of patient cohorts who were not included in this study.